2011
DOI: 10.1016/j.ejon.2011.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Informal caregiving in Hematopoietic Blood and Marrow Transplant patients

Abstract: Purpose-Hematopoietic cell transplant patients are among the most vulnerable and acutely ill cancer populations (Bevans, Mitchell, & Marden, 2008). The responsibility of caring for the daily physical and psychosocial needs of these patients after transplant is placed mostly on family caregivers (Williams, 2007). The purpose of this descriptive correlational research study was to describe caregiving experiences of 56 caregivers of HCT patients 3-12 months following transplant.Methods & Sample-Patients and careg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 42 publications
2
23
0
4
Order By: Relevance
“…The majority of studies indicated in either their titles or abstracts that caregiver burden was conceptually of interest, however, only four included a comprehensive multidimensional measure of burden (8, 2628). One additional study examined role strain (29) which is very closely linked conceptually to burden. Instead, 75% of studies examined specific correlates of burden, including anxiety and depression (27, 28, 3032), quality of life (29, 31), unmet needs (33), fatigue (27, 30, 32), and relationship quality (29, 30, 34).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies indicated in either their titles or abstracts that caregiver burden was conceptually of interest, however, only four included a comprehensive multidimensional measure of burden (8, 2628). One additional study examined role strain (29) which is very closely linked conceptually to burden. Instead, 75% of studies examined specific correlates of burden, including anxiety and depression (27, 28, 3032), quality of life (29, 31), unmet needs (33), fatigue (27, 30, 32), and relationship quality (29, 30, 34).…”
Section: Resultsmentioning
confidence: 99%
“…The dynamics of caregiving after HCT have been fairly well-documented for younger and older groups. The pediatric literature has focused on parental caregivers (Forinder, Claesson, Szybek, & Lindahl Norberg, 2015; Lindahl Norberg, Mellgren, Winiarski, & Forinder, 2014; Rodday et al, 2012; Virtue et al, 2014); meanwhile, adult studies report on spousal caregivers (Cooke, Grant, Eldredge, Maziarz, & Nail, 2011; Langer, Yi, Storer, & Syrjala, 2010; Meehan et al, 2006; Sabo, McLeod, & Couban, 2013; Wilson, Eilers, Heermann, & Million, 2009). Our findings suggest that the strongly dyadic relationship portrayed in both the pediatric and adult HCT research may not reflect the unique caregiving configurations of young adults.…”
Section: Discussionmentioning
confidence: 99%
“…Those in the immediate circle of patients who undergo HSCT are easily forgotten but are probably in need of better support. It has been shown that being a caregiver of a spouse undergoing HSCT is a heavy burden that entails psychological distress and a need for support (Beattie & Lebel, 2011;Cooke et al, 2011;Sabo et al, 2013).…”
Section: Quality Of Life In Hsct Patientsmentioning
confidence: 99%